THE INFLUENCE OF PRINCIPAL MANAGERIAL COMPETENCE AND WORK CLIMATE ON TEACHER PERFORMANCE IN STATE ELEMENTARY SCHOOL CULTURE 3, TANGERANG CITY - AULIANAH, Ulva (Journal of Education and Leadership in Education, 2023)
This study aims to prove: 1) the magnitude of the influence between the managerial competence of school principals on teacher performance; 2) The magnitude of the influence of work climate on teacher performance; 3) The magnitude of the influence of the managerial competence of school principals on the work climate. This research is a quantitative research. The method used in this research is a quantitative method with surveys and path analysis. The population in this study were teachers at the Gugus 3 Public Elementary School, Kota Tangerang, totaling 158 teachers with a sample of 113 teachers taken at random (proportional random sampling). The analysis technique used is path analysis technique. Based on the results of the research and discussion, it can be concluded: 1) There is a positive and significant direct effect of the principal's managerial competence on teacher performance. This is also proven from the results of tcount > ttable (14.864 > 1.982) and the path coefficient value of 0.562. 2) There is a positive and significant direct effect of work climate on teacher performance. This is also proven from the results of tcount > ttable (2.927 > 1.982) and the path coefficient value of 0.268. 3) There is a positive and significant direct effect on the managerial competency of the principal on the work climate.